A CASE-CONTROL STUDY OF PREVALENCE AND TYPE OF DYSLIPIDEMIA IN CHRONIC KIDNEY DISEASE - DR. M.V. BHARGAVI (International Journal of Pharma and Bio Sciences, 2015)
Chronic kidney disease, a worldwide health problem has extremely high morbidity and mortality from cardiovascular disease. Most patients succumb to cardiovascular disease before ever reaching stage 5 CKD. Our aim is to study the prevalence of dyslipidemia in chronic kidney disease, excluding diabetic and nephrotic aetiology and to compare it with the control population, to examine which type of hyperlipidemia predominates in these patients and to study whether any correlation exist between severity of CKD and lipid alteration. Hospital based 80 CKD patients, irrespective of aetiology except nephrotic proteinuria and diabetes mellitus excluding patients who are obese, on beta - blockers or oral contraceptive pills, pregnancy, smokers and alcoholics were age & sex matched with 80 normal healthy controls. Study group showed an increase in the total cholesterol, triglycerides & LDL and decrease in HDL when compared with the control population and the difference was significant by Odds ratio. Dyslipidemia was present in 45% of the study and 22.5% in the control group which was also significant by Odds Ratio (2.82). There was an increase in the prevalence of dyslipidemia in study group. Hence dyslipidemia should be treated from early stages of CKD to prevent the secondary complications.